Priprava bromobutilne gume za farmacevtske namene - Matijaševič, Mateja (Kovine zlitine tehnologije, 1997)
We were developing compound based on bromobutyl (BIIR) for pharmaceutical applications. Different fillers (calcinated clay, ?$CaCO_3$? covered by Ca-stearat) and their effect on compounds properties and vulcanizate were investigated. We have selected between following unconventional curing systems: resin, peroxide, amine and dieneophile cure.
Keywords: farmacija; pharmacy; kavčuk; vulkanizacija; vulkanizati; polnila